12 things to know about the Paleolithic Age - Marquardt, Meg (Marquardt, Meg. Prehistoric., 2020)
Describes twelve aspects of the Paleolithic Age, including the origins of humans in Africa and explains how these early humans traveled to other areas and eventually populated the world. Includes illustrations, a timeline, a glossary, and resources for further information.